PENDIDIKAN IMAN ANAK DALAM KELUARGA KATOLIK SERTA PEMBENTUKAN SIKAP KASIH SAYANG ANAK KEPADA ALLAH DAN SESAMA - Paskalita, Silvia; Wilhelmus, Ola Rongan (Lembaga Penelitian STKIP Widya Yuwana, 2025)
In the family, parents have an irreplaceable role in educating the Catholic faith of their children. Faith education in a Catholic family does not only provide knowledge about the Catholic faith to the children, but also to form children's loving attitudes. The research aims to explore the role of parents in children's faith education and the formation of children's loving attitudes towards God and others, as well as to analyze the challenges and solutions related to the children's faith education. The research applies a qualitative method with a descriptive approach. Data was collected through direct interviews with informants selected purposively. The results of the research show that Catholic faith education in the family has a significant influence on the formation of children's loving attitudes towards God and others. However, parents are continuously facing some challenges related to the Catholic faith education for their children. Those challenges are including time limitation to gather with the family due to huge activities of the parents and limited knowledge of parents regarding Catholic faith. To respond the challenges, parents continuously try their best to provide Catholic faith education for their children by encouraging them to join prayer activities in the family, attending Eucharist celebrations, increasing communication and mutual understanding among the family members.